The sceptics - Hankinson, R. J. (Arguments of the philosophers., 1998)
The first comprehensive, up-to-date treatment of Greek sceptism, from the beginnings of epistemology with Xenophanes, to the final full development Pyrrhonism as presented in the work of Sextus Empiricus.